Perception of Nursing Faculty Towards Their Preferred Profession Across the India: A Cross Sectional Descriptive Study - V. A. Raghu; S K Mohana Sundari (Journal of Integrated Health Sciences)
Background: India is the country that produces the majority of nurses, and nurses are the core of the country's health-care system. The nurses can pursue a career in clinical work or teaching. The performance of the nursing faculties is significantly influenced by their perception toward preferred profession. The objective of the study was to assess the perception of nursing faculties toward their preferred profession. Methodology: All four areas of India – the east, west, north, and south - were covered in a cross-sectional descriptive study that involved 300 nursing faculties. The samples were contacted through direct approach and electronic mode by circulating the survey link created by SurveyMonkey App. Five-point Likert scale, which comprises total 15 statements, was used to collect data. After filling informed consent, the participants were asked to fill the questionnaire. Results: Nearly 2/3rd of the subjects (188) had a favorable perception toward their preferred profession and more than 1/3rd (112) of them had an unfavorable perception. Binary logistic regression analysis indicated that marital status (P = 0.000; adjusted odds ratio [AOR]: 0.100; 95% confidence interval [CI]: 0.36–0.280), qualification (P = 0.010; AOR: 2.194; 95% CI: 1.205–3.993), and clinical experience (P = 0.011; AOR: 2.013; 95% CI: 1.173–3.454) had a significant influence the perception of faculty. Conclusion: Almost half of the subjects expressed negative perceptions. Although perception is a personal psychological factor, the government, professional bodies, and nurse managers can take the necessary steps to address the issue that dissatisfy nursing faculty can promote positive perception and that would impact their high-quality performance.